GENDER-BASED USE OF EUPHEMISMS IN THE KARAKALPAK LANGUAGE - Babaniyazova Nursulıw Konısbayevna (International Journal of Literature and Language Studies, 2026)
This article analyzes the gender-based features of euphemism usage in the Karakalpak language from sociolinguistic and pragmatic perspectives. The study examines the use of euphemisms by men, women, and gender-neutral speakers across thematic groups (marriage, indecency, intimate relations, forms of address, physical disabilities, aging, death, etc.). The results show that euphemisms are closely connected with gender roles, social norms, and communicative strategies. Women’s speech is characterized by politeness, softness, and emotional sensitivity, while men’s speech tends to be more direct and informative.